Dendrimer size effects on the selective brain tumor targeting in orthotopic tumor models upon systemic administration - Kevin Liaw; Fan Zhang; Antonella Mangraviti; Sujatha Kannan; Betty Tyler; Rangaramanujam M. Kannan (Wiley, 2020)
Abstract Malignant gliomas are the most common and aggressive form of primary brain tumors, with a median survival of 15-20 months for patients receiving maximal interventions. Advances in nanomedicine have provided tumor‐specific delivery of chemotherapeutics to potentially overcome their off‐target toxicities. Recent advances in dendrimer‐based nanomedicines have established that hydroxyl‐terminated poly(amidoamine) dendrimers can intrinsically target neuroinflammation and brain tumors from systemic administration without the need for targeting moieties. The size of nanocarriers is a critical parameter that determines their tumor‐targeting efficiency, intratumor distribution, and clearance mechanism. In this study, we explore the dendrimer size effects on brain tumor targeting capability in two clinically relevant orthotopic brain tumor models, the 9L rat and GL261 mouse models, which capture differing aspects of gliomas. We show that increasing dendrimers from Generation 4 to Generation 6 significantly enhances their tumor accumulation (~10‐fold greater at 24 hr), tumor specificity (~2-3 fold higher), and tumor retention. The superior tumor targeting effect of G6 dendrimers is associated with its reduced renal clearance rate, resulting in longer circulation time compared to G4 dendrimers. Additionally, the increase in dendrimer generation does not compromise its homogeneous tumor distribution and intrinsic targeting of tumor‐associated macrophages. These results validate the potential for these dendrimers as an effective, clinically translatable platform for effectively targeting tumor‐associated macrophages in malignant gliomas.